Pulmonary tuberculosis risk stratification in communities of the Abreus municipality. Cienfuegos, 2015 - Tamara Montenegro Calderón; Adrián Bermúdez Novoa; Narciso Águila Rodríguez; Hilda María Delgado Acosta; Sadis Suárez del Villar Seuret (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Tuberculosis is a priority research topic in Cuba, given the need to strengthen the response capacity for its elimination as a health problem. Objective: to stratify the risk of pulmonary tuberculosis in communities of the Abreus municipality. Methods: a descriptive study was carried out in the seven communities of the Abreus municipality, Cienfuegos province, during 2015. The information was obtained from the statistical departments of the health areas and the Municipal Hygiene and Epidemiology Unit. The absolute risk distribution method was used. The criterion for the stratification taken into account to define the high, medium and low risk strata was the average prevalence of risk factors according to the identified patients in 2015. The risk analyzed factors were: population over 60 years, contact rate of patients with pulmonary tuberculosis, prevalence of acquired immunodeficiency virus/AIDS, alcoholics, social hardship cases, smokers, and diabetics. The MapInfo 7.5 program was used. Results: the prevalence of smoking was high, with 5 communities located in the medium riskstratum, one in the low risk stratum, and another (Cieneguitas) in the high risk stratum. Communities of Abreus, Charca, Cieneguita and Yaguaramas presented the highest percentage of factors located in the high risk stratum. Conclusion: Clinical epidemiological characteristics of the cases reported with pulmonary tuberculosis in the decade 2006-2015, in Abreus, show evidence of the potential risk of tuberculosis infection in the community.